An Assessment of Ground Level and Free Tropospheric Ozone Over California and Nevada. Issue 18 (19th September 2017) - Yates, E. L.; Johnson, M. S.; Iraci, L. T.; Ryoo, J.‐M.; Pierce, R. B.; Cullis, P. D.; Gore, W.; Ives, M. A.; Johnson, B. J.; Leblanc, T.; Marrero, J. E.; Sterling, C. W.; et al.
Abstract: Increasing free tropospheric ozone (O3 ), combined with the high elevation and often deep boundary layers at western U.S. surface stations, poses challenges in attaining the more stringent 70 ppb O3 National Ambient Air Quality Standard. As such, use of observational data to identify sources and mechanisms that contribute to surface O3 is increasingly important. This work analyzes surface and vertical O3 observations over California and Nevada from 1995 to 2015. Over this period, the number of high O3 events (95th percentile) at the U.S. Environmental Protection Agency Clean Air Status and Trends Network (CASTNET) sites has decreased during summer, as a result of decreasing U.S. emissions. In contrast, an increase in springtime 5th percentile O3 indicates a general increase of baseline O3 . During 2012 there was a peak in exceedances and in the average spring‐summer O3 mixing ratios at CASTNET sites. Goddard Earth Observing System‐Chem results show that the surface O3 attributable to transport from the upper troposphere and stratosphere was increased in 2013 compared to 2012, highlighting the importance of measurements aloft. Vertical O3 measurements from aircraft, ozonesondes, and lidar show distinct seasonal trends, with a high percentage of elevated O3 laminae (O3  > 70 ppb, 3–8 km) during spring and summer. Analysis of the timing of high O3 surface events and correlation between surface and vertical O3 data is used to discuss varying sources of western U.S. surface O3 . Key Points: Modeling results suggest that 2012 elevated O3 at surface sites is associated with increased exposure to upper troposphere and lower stratosphere In spring 72% and summer 65% of O3 vertical profiles have elevated O3 lamina (3‐8 km, O3 > 70 ppb) Observational analysis highlights importance of both surface O3 and O3 aloft in understanding the varying sources of O3 in the western U.S.